Nursing workers: achievement of formalization, hard work and collective action dilemas - Souza, Helton Saragor de; Mendes, Áquilas Nogueira; Chaves, Alessandro Rodrigues (Ciência & saude coletiva, 2020)
The singularity of the collective action of nursing categories in sociopolitical participation is the subject of our analysis. This paper attaches the compelling factors of social origin and aspects of the labor market to the political action of professionals. Based on the analytical association of the extended case method, we articulated the interpretation of the database of the Brazilian Nursing Profile Survey, specifically, in the light of socioeconomic identification, labor market, and working conditions, with an ethnographic study and semi-structured interviews in three hospital units. The bibliographic review shows the incorporation of these individuals without underestimating their particularity: the historical process of proletarianization in the Brazilian social formation, the inclusion of women in the labor market, and the relationship with unions. The history of workers based on inexperience in actions of resistance or union representation associated with the valorization of employment as a social ascent results in asymmetrical work regimes, a hindering element to coordinated actions, a fundamental aspect for the improvement of working conditions.